Motion – Patients with Primary Sclerosing Cholangitis Should Undergo Early Liver Transplantation: Arguments against the Motion - Jeffrey S Crippin (Canadian Journal of Gastroenterology)
Liver transplantation is an accepted form of treatment for patients with primary sclerosing cholangitis (PSC) and can provide long term survival. Cholangiocarcinoma occurs in 10% to 20% of patients with PSC, is difficult to diagnose and has a poor prognosis. It has been proposed that liver transplantation be undertaken early in the course of the PSC, before cancer develops. Such a proposal would have significant implications for the method of assigning priority to patients awaiting liver transplantation. Other patients on the waiting list would experience further delays, while there is no proven benefit for PSC patients. Few patients with this disease are removed from the waiting list because they developed cancer. If one were to state that PSC patients warrant special consideration because of the hypothetical risk of cholangiocarcinoma, the same argument could be applied to patients with hepatitis C and other causes of cirrhosis, who are at increased risk of hepatocellular carcinoma. The transplant allocation system is applied in an equitable fashion to patients with a large variety of liver diseases. Alteration of this system to benefit a small number of patients with PSC would violate the principles on which it was created, and cannot be justified.